Elaboration of metal organic framework hybrid materials with hierarchical porosity by electrochemical deposition–dissolution. Issue 27 (17th June 2016) - Warakulwit, Chompunuch; Yadnum, Sudarat; Boonyuen, Chaiyan; Wattanakit, Chularat; Karajic, Aleksandar; Garrigue, Patrick; Mano, Nicolas; Bradshaw, Darren; Limtrakul, Jumras; Kuhn, Alexander
Abstract : Rationally designed MOF materials with hierarchical porosity are prepared via an electrochemical deposition–dissolution technique, leading to hybrid Cu/HKUST-1 layers. Abstract : Rationally designed hierarchical macro-/microporous HKUST-1 electrodes were prepared via an electrochemical deposition–dissolution technique with the motivation to overcome diffusion limitations that typically occur for conventional microporous MOFs. A colloidal crystal of silica spheres was prepared by the Langmuir–Blodgett (LB) technique. Using this crystal as a template, macroporous copper electrodes with a controlled number of pore layers were prepared via electrodeposition. After the removal of the template, the synthesis of HKUST-1 was performed via partial anodic dissolution of the copper surface in the presence of an organic linker, leading to the deposition of HKUST-1 on the electrode surface with the designed macroporous structure. The macroporous Cu electrodes do not only behave as structural templates but are also the Cu source for the formation of MOFs. The applied potential and deposition time allow the characteristics of the porous layer to be fine-tuned. The developed synthesis is rapid, occurs under mild conditions and therefore opens up various potential applications including catalysis, separation and sensing based on these hierarchical materials.